Public Service Accountability - Murphy, Peter. author. aut Link
XIII, 146 p. 7 illus.
Keywords: "This book makes a fantastic contribution to the literature and practice of accountability in public services. It will definitely be of interest and use to practitioners, academics, and policymakers." —Adina Dudau, University of Glasgow, UK "It is high time that we reopen this critical debate and this book certainly does that. It advances polemical and clearly articulated perspectives that should provoke valuable discussion within the academic and practitioner communities." —Joyce Liddle, Northumbria University, UK How we manage public services and hold them to account is critically important. Yet austerity, recent changes to accountability frameworks, and the loss of the Audit Commission have created a huge deficit in our understanding of how well services are delivered. The time is thus right to re-examine the state of our vital public services, as well as how we can make them more accountable. This book reopens the debate on what accountability means and provides unique insights into an increasingly complex organizational landscape. It presents a new and innovative way of evaluating public services that should be of use to academics and public servants alike. Synthesising empirical work across local government, health and social care, the police, and fire services, this book also explores the relationship between financial and performance accountability and makes the case for the need for a distinctive sense of public service accountability. Pete Murphy is Professor of Public Policy and Management at Nottingham Business School. He was a senior civil servant and the chief executive of a local authority. Laurence Ferry is Professor of Accounting at Durham University. He is a well-recognised international expert in public financial management. Russ Glennon is a Senior Lecturer in management and leadership at Nottingham Business School, Nottingham Trent University and specialises in public policy and management. Kirsten Greenhalgh is Associate Professor of Accounting at Nottingham University Business School and has a professional background in management accounting in the NHS and local government.